Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/mao.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation for Patients With Single-Sided Deafness or Asymmetrical Hearing Loss

Abstract: There are no high-level-of-evidence studies concerning cochlear implantation in patients with SSD or AHL. Current literature suggests important benefits of cochlear implantation regarding sound localization, QoL, and tinnitus. Varying results were reported for speech perception in noise, possibly caused by the large clinical heterogeneity between studies. Larger and high-quality studies are certainly warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 39 publications
(63 reference statements)
6
94
0
2
Order By: Relevance
“…High-level-of-evidence studies concerning CI in patients with SSD are sparse, although the current literature suggests important benefits regarding sound localization, QoL, and tinnitus [16]. Furthermore, its cost-effectiveness may be questionable, since most SSD patients manage well without any rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…High-level-of-evidence studies concerning CI in patients with SSD are sparse, although the current literature suggests important benefits regarding sound localization, QoL, and tinnitus [16]. Furthermore, its cost-effectiveness may be questionable, since most SSD patients manage well without any rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Contralateral rerouting of signal (CROS) hearing aids [Bosman et al, 2003;Finbow et al, 2015;Hol et al, 2005;Wazen et al, 2003] and percutaneous bone-anchored hearing devices [Faber et al, 2013;Martin et al, 2010;Stewart et al, 2011;Zeitler et al, 2012] have been proposed for the rehabilitation of SSD with different results. More recently, cochlear implant has been suggested for the rehabilitation of SSD [Arndt et al, 2011;Erbele et al, 2015;van Zon et al, 2015;Vermeire and Van de Heyning, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…when speech is directed towards the implanted ear and noise towards the non-implanted ear (Blasco and Redleaf, 2014;van Zon et al, 2015). In this listening situation, use of the implant allows the patient to access a copy of the speech signal that is less degraded than that which is accessible using their better ear alone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were identified from existing systematic reviews that assessed the evidence for cochlear implantation in adults with unilateral deafness or highly asymmetric hearing loss (Blasco and Redleaf, 2014;Kitterick et al, 2015;van Zon et al, 2015). These reviews were identified through title and abstract searches of the Medline, EMBASE, PubMed, and Cochrane Library databases.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation